Codon-Reduced Protein Synthesis With Manipulating tRNA Components in Cell-Free System - Li, Jiaojiao; Tang, Mengtong; Qi, Hao (Frontiers in Bioengineering and Biotechnology, 2022)
Manipulating transfer RNAs (tRNAs) for emancipating sense codons to simplify genetic codons in a cell-free protein synthesis (CFPS) system can offer more flexibility and controllability. Here, we provide an overview of the tRNA complement protein synthesis system construction in the tRNA-depleted Protein synthesis Using purified Recombinant Elements (PURE) system or S30 extract. These designed polypeptide coding sequences reduce the genetic codon and contain only a single tRNA corresponding to a single amino acid in this presented system. Strategies for removing tRNAs from cell lysates and synthesizing tRNAs in vivo/vitro are summarized and discussed in detail. Furthermore, we point out the trend toward a minimized genetic codon for reducing codon redundancy by manipulating tRNAs in the different proteins. It is hoped that the tRNA complement protein synthesis system can facilitate the construction of minimal cells and expand the biomedical application scope of synthetic biology.